On the multiplicity of the zero-age main-sequence O star Herschel 36 - Arias, Julia Ines (2010)
We present the analysis of high-resolution optical spectroscopic observations of the zero-age main-sequence O star Herschel 36 spanning six years. This star is definitely a multiple system, with at least three components detected in its spectrum. Based on our radial-velocity (RV) study, we propose a picture of a close massive binary and a more distant companion, most probably in wide orbit about each other. The orbital solution for the binary, whose components we identify as O9 V and B0.5 V, is characterized by a period of 1.5415 ± 0.0006 days. With a spectral type O7.5 V, the third body is the most luminous component of the system and also presents RV variations with a period close to 498 days. Some possible hypotheses to explain the variability are briefly addressed and further observations are suggested.